How enhancing gender inclusion affects inequality: Thresholds of complementary policies for sustainable development - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study investigates how enhancing gender inclusion affects inequality in 42 African countries for the period 2004-2014. The empirical evidence is based on the Generalized Method of Moments. Three inequality indicators are used, namely, the: Gini coefficient, Atkinson index, and Palma ratio. The two gender inclusion measurements used include female labour force participation and female employment. The following main findings are established. There are positive net effects on inequality from the enhancement of gender inclusion dynamics. An extended threshold analysis is used to assess critical masses at which further increasing gender inclusion enhances inequality. The established thresholds are: (i) 55.555 "employment to population ratio, 15+, female (%)"for the nexus with the Gini coefficient. (ii) 50 "labor force participation rate, female (% of female population ages 15+)" and between 50 to 55 "employment to population ratio, 15+, female (%)", for the Atkinson index. (iii) 61.87 "labor force participation rate, female (% of female population ages 15+)" for the Palma ratio.These established thresholds are worthwhile for sustainable development because, beyond the critical masses, policy makers should complement the gender inclusion policy with other measures designed to reduce income inequality. Some complementary measures that can be taken on board beyond the established thresholds could focus on enhancing, inter alia: information and communication technology, infrastructural development; financial inclusion and inclusive education.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Gender; Inclusive development; Sustainable development